2022
DOI: 10.1111/jth.15703
|View full text |Cite
|
Sign up to set email alerts
|

α‐hemolysin of Staphylococcus aureus impairs thrombus formation

Abstract: Background: Toxins are key virulence determinants of pathogens and can impair the function of host immune cells, including platelets. Insights into pathogen toxin interference with platelets will be pivotal to improve treatment of patients with bacterial bloodstream infections. Materials and Methods: In this study, we deciphered the effects of Staphylococcus aureus toxins α-hemolysin, LukAB, LukDE, and LukSF on human platelets and compared the effects with the pore forming toxin pneumolysin of Streptococcus pn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…IVIG is a blood product containing IgG derived from large plasma pools obtained from thousands of blood donors [52]. It contains anti-PLY antibodies [53] and our data here suggest that IVIG also contains antibodies against pneumococcal neuraminidases (Figure S7). The advantage of IVIG is that it is readily available in most hospitals and that it is inhibiting both, pneumolysin and neuraminidase(s) and probably also targets other pneumococcal proteins [33].…”
Section: Accepted Manuscriptmentioning
confidence: 56%
“…IVIG is a blood product containing IgG derived from large plasma pools obtained from thousands of blood donors [52]. It contains anti-PLY antibodies [53] and our data here suggest that IVIG also contains antibodies against pneumococcal neuraminidases (Figure S7). The advantage of IVIG is that it is readily available in most hospitals and that it is inhibiting both, pneumolysin and neuraminidase(s) and probably also targets other pneumococcal proteins [33].…”
Section: Accepted Manuscriptmentioning
confidence: 56%
“… 11 A recent study indicated that the presence of small amounts of α-toxin in blood abrogates thrombus formation. 31 Thus, limiting α-toxin production to subcytolytic levels might inhibit platelet-dependent vegetation formation. In contrast, at cytolytic concentrations, α-toxin causes aberrant platelet activation and aggregation, as a bacterial immune evasion mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of platelets with Hla have been reported to cause platelet activation and aggregation [ 98 , 99 ]. In addition, we recently demonstrated that Hla-mediated platelet activation is followed by loss of platelet function, leading to impaired thrombus formation and reduced stability of formed thrombi [ 100 ].…”
Section: Platelet Receptors In Bacterial Infections and Bacterial Adh...mentioning
confidence: 99%